ETNOMATEMATIKA PADA ALAT MUSIK TRADISIONAL BANYUWANGI SEBAGAI BAHAN AJAR SISWA - Andarini, Firda Febri; Sunardi, S; Monalisa, Lioni Anka (Kadikma, 2019)
The purpose of this study was to describe ethnomatematics in Banyuwangi traditional musical instruments and produce student teaching materials in the form of student worksheets. This type of research is qualitative research with an ethnographic approach. Data collection methods used are observation and interviews. The subject of this study was one cultural person. Ethnomatematics that appear in Banyuwangi traditional musical instruments are found in the shape and size of Banyuwangi musical instruments. This study focused on several objects. The objects in question are kendang, saron, bonang, gong, angklung, and kluncing. The mathematical concepts that appear in Banyuwangi traditional music instruments are geometric shapes, congruent, and arithmetic sequences. The student worksheets are intended for class VIII Middle School / MTs students with triangular material and for class IX with cone material and arithmetic sequences. Keywords: Ethnomatematics, Banyuwangi Traditional Musical Instruments, Geometry